Development of Insurance Planning System (IPS) using artificial intelligence technique / Muhammad Asyrafhaziq Johari - Johari, Muhammad Asyrafhaziq (2017)
Today, selecting the suitable insurance policy is complex and more difficult with many option and criteria. Using Artificial Intelligence Technique in developing the Insurance Planning System (IPS) can guide customer in their selection. Before the system is developed, a review on artificial intelligence has been carried out in order to determine which technique is suitable and rule base system is the technique used. Interview session with the experts to determine the user factors. Factors determined are age, gender, BMI index, occupation level, annual income, smoking status and type provided the main impact on determining the insurance policy. The relationship between insurance policy and user factors is formulated using rule-based approach, and managed properly. IPS is developed as a web-based application using evolutionary prototyping and evaluated by user based on its usability, functionality and quality. The outcome of the evaluation shows that the system can assist them in deciding which insurance is suitable. As a result, a prototype of IPS is produced together with documentation of Software Requirement Specification (SRS) and Software Design Document (SDD).